EFFECT OF E-PROMOTION -SOCIAL MEDIA AND E-WOM TOWARD INTENTION OF USING E-MONEY JAMBI CITY - Ade Erma Suryani; Musnaini Musnaini; Tona Auora Lubis (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The purpose of this study is to explain the direct and indirect relationship of the influence of e-Promotion Social Media and e-WoM mediated by e-Service Quality on interest in using e-Money in Jambi City. The research methodology uses a confirmatory approach and inferential quantitative analysis techniques. The sample used is 100 as respondents who fill out the questionnaire. The results of the study prove that directly e-Promotion using social media and e-WoM has a significant positive effect on interest in using e-Money. But indirectly e-Service Quality mediated only e-Promotion using social media, the hypothesis is proven and accepted. The conclusion of this study is that e service quality has a partial meditation role.